Pengembangan Bahan Ajar Interaktif Berbasis Problem Based Learning untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik - Ferry Irawan; Dharma Gyta Sari Harahap; Muh. Rafi’y (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research aims to develop PBL-based interactive teaching materials to improve students' scientific literacy skills. The teaching materials developed have met validity and practicality and can be used in class IX Mts Loppe Luwu Regency. The research method used is Research and Development (R&D) with the ADDIE model. Data was collected through assessments by experts in the fields of materials, design and learning media. The research instruments used were questionnaires, interview guides and observation sheets. The data analysis techniques used are descriptive quantitative and qualitative. The results of the development of this interactive teaching material have been assessed as valid based on references from expert validators. It can be concluded that the interactive teaching materials developed by researchers are suitable for use in the learning process in class IX Mts Loppe Luwu Regency